Manejemen Implementasi Kurikulum Merdeka Belajar di SMP Negeri 1 Sitellu Tali Urang Jehe Pakpak Bharat - Gultom, Sri Wahyuni; Amini, Amini; Isman, Muhammad (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
The aim of this research is to find out: Management planning for the implementation of the independent learning curriculum at SMP Negeri 1 Sitellu Tali Urang Jehe Pakpak Bharat. Implementation of management of the implementation of the independent learning curriculum at SMP Negeri 1 Sitellu Tali Urang Jehe Pakpak Bharat and Evaluation of implementation management of the independent learning curriculum at SMP Negeri 1 Sitellu Tali Urang Jehe Pakpak Bharat.. This research method is qualitative research. Data collection was carried out by documentation, observation and interviews. Data analysis techniques use data reduction, data presentation and conclusions. The research results and conclusions are 1) Management planning for the implementation of the independent learning curriculum at SMP Negeri 1 Sitellu Tali Urang Jehe Pakpak Bharat has not been optimal, where thorough preparation starting from compiling teaching modules has not yet been done by a separate teacher, but the teacher already understands the learning outcomes, ATP, then assessment. Then the use of learning models is also not optimal because differentiated learning has not been implemented. Regarding teaching media and teaching materials, teachers have used them, however, this is not the work of the teachers themselves. 2) The implementation of the Independent Learning curriculum at SMPN 1 Sitellu Tali Urang Jehe means that the teacher has created a teaching module and understands the content in this teaching module, but the teaching module created by the teacher is not in accordance with the teacher's manual in hand. For learning media, teachers have used innovative video-based media, but the videos used are not their own work. Regarding the implementation learning model, some teachers have used innovative learning models, but some still use conventional models. 3) The evaluation carried out takes the form of supervision, where supervision is carried out by the school principal to evaluate the extent to which the implementation of the Merdeka curriculum is implemented. Then a work shop was also held, in the workshop also carried out evaluations for teacher progress. However, supervision is only carried out once per semester, and this is considered less effective in adapting to teacher needs in implementing the Merdeka Belajar curriculum.